L’antiféminisme de gauche – un syndrome révisionniste - Dixon, Marlene (Revue PréfiX, 2024)
Même si la misogynie et les agressions sexuelles sont des problèmes bien connus et depuis longtemps dénoncés par des féministes militant dans les réseaux de gauche et d’extrême-gauche, les textes d’analyse sur l’antiféminisme de gauche restent relativement rares dans la vaste production d’études sur l’antiféminisme en général
Keywords: 1800-1899; 1900-1999; amériques; antiféminisme; approches et analyses; capitalisme; communisme; cours; discipline; droits des femmes*; féminisme matérialiste; gauche; patriarcat; pol5185; premier cycle; prolétariat; préFiX; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; traduction; travail; violences; états-unis

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Théorie de la politique sexuelle - Millett, Kate (La politique du mâle, 1971)
Réédition d'un ouvrage paru chez le même éditeur en 1971. C'est une analyse critique d'une certaine envergure, souvent virulente et parfois contestée, de la prétendue supériorité du mâle. Trois parties bien distinctes : 1. La politique sexuelle. L'auteur dégage l'aspect politique souvent négligé de la sexualité. C'est le sujet de la thèse soutenue par l'auteur, à partir des concepts de puissance et de domination utilisés dans les relations entre les sexes - 2. L'arrière-plan historique. Fait ressortir les transformations de la relation entre les sexes : la révolution sexuelle entre 1830 et 1930; le climat de réaction entre 1930 et 1960 - 3. Le reflet littéraire. Etude basée sur la critique littéraire. L'auteur y montre comment quatre écrivains, Lawrence, Miller, Mailer et Genet, ont contribué à perpétuer l'idée de domination masculine. Importante bibliographie.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cours; fem1000; féminisme matérialiste; féminisme radical; patriarcat; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis